Neem (Azadirachta indica A. Juss) supplemented biofloc medium as alternative feed in common carp (Cyprinus carpio var. communis Linnaeus) culture. Issue 4 (1st October 2020) - Dinda, Riya; Mandal, Amit; Das, S. K.
ABSTRACT: The potential of neem, Azadirachta indica (A. Juss), supplemented biofloc medium in replacement of costly feed for Cyprinus carpio culture vis-à-vis the environmental health of the system was investigated. The biofloc-supported culture system resulted in 17% more growth, parallel with improvement in feed conversion ratio and efficiency by 32.56% and 14.11% respectively. However, biofloc alone could not support growth and survival of the test fish, as higher (P < .05) mortality (22.22%) was encountered. In spite of nitrification inhibition in neem-based biofloc medium, the nutrient status of the system was not impacted. Bioflocs favored phosphorus mineralization and became limited in maintaining the balance between available nitrogen: phosphorus beyond 0.065 mg L −1 .